2021
DOI: 10.1093/annweh/wxab040
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems as a Risk Factor for Workplace Bullying: The Protective Effect of a Well-Functioning Organization

Abstract: This study examined a strain–stressor association, when mental health problems may lead to subsequent workplace bullying, and a mechanism of how this can happen. I hypothesized that the association between mental health problems and bullying depends on the perceived role clarity and order in the organization, and that sickness presenteeism (SP) mediates this association. The study is based on a longitudinal probability sample drawn from the total number of employees in Sweden. Workplace bullying, mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…18 Sickness presenteeism is known to be associated with poor mental health among workers. 19 Workers who engage in frequent sickness presenteeism are reported to have a higher risk of developing depression in the future. 20 The reasons are thought to include worsening relationship with superiors and colleagues due to decreased work efficiency and poor sleep.…”
Section: Discussionmentioning
confidence: 99%
“…18 Sickness presenteeism is known to be associated with poor mental health among workers. 19 Workers who engage in frequent sickness presenteeism are reported to have a higher risk of developing depression in the future. 20 The reasons are thought to include worsening relationship with superiors and colleagues due to decreased work efficiency and poor sleep.…”
Section: Discussionmentioning
confidence: 99%
“…RIM is based on six items focussing on: The RIM was used as a control variable in the study. Its psychometric properties have been explored (Rosander & Blomberg, 2018), and associations to other relevant measures have been established (Rosander, 2021;Rosander & Blomberg, 2019).…”
Section: Unclear Roles In the Organizationmentioning
confidence: 99%
“…One could argue that the association between individual causes and bullying may depend on the work environment in such a way that individual characteristics may only be associated with subsequent bullying in organization lacking in role clarity or leadership. For example, in a recent study, Rosander (2021) showed that the association between mental health problems, a known individual risk factor for bullying, and subsequent bullying, only was present if there were also organizational deficits present. Regardless of cause, workplace bullying is a long‐lasting phenomenon.…”
Section: Bullying Job Change and Consequencesmentioning
confidence: 99%